2020
DOI: 10.1016/j.jjcc.2019.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Impact of high-sensitivity C-reactive protein on coronary artery disease severity and outcomes in patients undergoing percutaneous coronary intervention

Abstract: Coronary artery disease (CAD) is a leading cause of mortality and morbidity worldwide. The calculation of SYNTAX (Synergy between PCI with TAXUS and Cardiac Surgery) score (SS) in angiography has been widely accepted to grade the complexity of CAD and aid in choosing revascularization strategy with either coronary artery bypass grafting (CABG) or percutaneous coronary intervention (PCI) [1]. It is acknowledged that inflammation plays a pivotal role in atherosclerosis and more important, contributes to instabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 44 publications
0
25
0
Order By: Relevance
“…Four studies investigated the relationship between PLR and CSF 23 26 ; 423 SCF patients and 485 controls were included in meta-analysis. Since the I 2 for the studies was 95%, random effects model was chosen to evaluate MD in 2 groups. Overall, SCF patients had a higher PLR than those with normal coronary flow (MD: 49.01, 95% CI: 11.10-86.92, P = .01; Figure 5).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Four studies investigated the relationship between PLR and CSF 23 26 ; 423 SCF patients and 485 controls were included in meta-analysis. Since the I 2 for the studies was 95%, random effects model was chosen to evaluate MD in 2 groups. Overall, SCF patients had a higher PLR than those with normal coronary flow (MD: 49.01, 95% CI: 11.10-86.92, P = .01; Figure 5).…”
Section: Resultsmentioning
confidence: 99%
“…1 Therefore, it is not surprising that inflammatory biomarkers such as neutrophil and platelet counts, red blood cell distribution width, neutrophil to lymphocyte ratio, platelet to lymphocyte ratio (PLR) are elevated in patients with coronary artery disease (CAD). [2][3][4][5] Platelets play an important role in the development of atherosclerosis. 6 They release immunomodulatory mediators, such as prostaglandin E2, platelet-activating factor, which contribute to inflammation.…”
Section: Introductionmentioning
confidence: 99%
“… 30 Higher CRP levels increase the risk of hypertension and cerebrovascular disease. 31 In this study, we found that VEGF and eNOS expression in plasma and placental tissues from pregnancy-induced hypertension rats were lower, but CRP levels were higher compared with the control group. Therefore, our results indicated that pregnancy-induced hypertension is associated with vascular endothelial injury.…”
Section: Discussionmentioning
confidence: 52%
“…The hsCRP level has been reported to be associated with Syntax score. [25][26][27] MHR was initially discovered to be associated with cardiovascular outcomes and was identified as an independent predictor of major adverse cardiovascular events in patients with chronic kidney disease. 28 The positive correlation of MHR with Syntax score in patients with stable CAD has been identified in several studies.…”
Section: Discussionmentioning
confidence: 99%